2022
DOI: 10.3390/cells11010161
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type-Selective Loss of Peroxisomal β-Oxidation Impairs Bipolar Cell but Not Photoreceptor Survival in the Retina

Abstract: Retinal degeneration is a common feature in peroxisomal disorders leading to blindness. Peroxisomes are present in the different cell types of the retina; however, their precise contribution to retinal integrity is still unclear. We previously showed that mice lacking the central peroxisomal β-oxidation enzyme, multifunctional protein 2 (MFP2), develop an early onset retinal decay including photoreceptor cell death. To decipher the function of peroxisomal β-oxidation in photoreceptors, we generated cell type s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 61 publications
(115 reference statements)
1
23
0
Order By: Relevance
“…Despite the continued ONL thinning, there was significant recovery of the a- and b-waves, indicating that there may be some plasticity in the signaling of the retina. This type of plasticity or recovery has been noted before in rodent models of degeneration [ 14 , 27 ], and bipolar cell sprouting is a potential contributing factor [ 28 , 29 ]. An electron microscopic examination of the outer plexiform layer could confirm synaptic remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…Despite the continued ONL thinning, there was significant recovery of the a- and b-waves, indicating that there may be some plasticity in the signaling of the retina. This type of plasticity or recovery has been noted before in rodent models of degeneration [ 14 , 27 ], and bipolar cell sprouting is a potential contributing factor [ 28 , 29 ]. An electron microscopic examination of the outer plexiform layer could confirm synaptic remodeling.…”
Section: Discussionsupporting
confidence: 57%
“…At the end of our study, ONL thickness showed a persistent 22% loss, but the b-wave had recovered. Other investigators have noted b-wave recovery after photoreceptor loss [17,23,24] and retinal remodeling is known to occur following photoreceptor loss [25][26][27], which may explain the recovery of b-wave amplitudes. Considering the similar loss of the b-wave amplitude in the RCS (PN23) and light-damaged albino rats (R6), we expected to see greater reductions in ERG CFF in the light-damaged rats.…”
Section: Discussionmentioning
confidence: 90%
“…However, the exact mechanistic association between MFP2 deficiency and retinopathy remained unclear (Das et al, 2021b). To decipher which cell-type was responsible for this phenotype, mice lacking MFP2 specifically in both photoreceptors and bipolar cells (Crx-Mfp2 − /− ) were studied (Swinkels et al, 2022). These mice presented with impaired photoreceptor synaptic integrity and reduced rod bipolar cell (RBC) survival and functioning.…”
mentioning
confidence: 99%
“…Both mouse strains were of C57BL6 background. Genotyping was performed as previously described (Swinkels et al, 2022). To investigate the Cre-recombination pattern in L7-Mfp2 − /− mice, they were crossed with mT/mG reporter mice (Muzumdar et al, 2007), kindly supplied by the laboratory of Angiogenesis and Vascular Metabolism (KU Leuven-VIB).…”
mentioning
confidence: 99%
See 1 more Smart Citation